2020
DOI: 10.1007/s40817-020-00076-5
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Correlates of Adolescent Cannabis Use: an Overview of Neural Activation Patterns in Task-Based Functional MRI Studies

Abstract: Alcohol and cannabis use are highly prevalent among adolescents and associated with negative consequences. Understanding motivations behind substance use in youth is important for informing prevention and intervention efforts. The present study aims to examine negative reinforcement principles of substance use among adolescent cannabis and alcohol users by pairing a cue reactivity paradigm with an aversive interoceptive stimulus. Adolescents (ages 15-17), classified as controls (CTL; n = 18), cannabis and/or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 132 publications
(89 reference statements)
0
7
0
Order By: Relevance
“…Further, prior research indicates cannabis users may be particularly vulnerable to cognitive control and affective processing deficits, including when identifying emotional faces [ 59 ]. Cannabis users may have to use more neural resources to achieve the same level of performance [ 60 ], though this may not happen as readily on a less demanding task, such as on a congruent processing task. Future research should continue to investigate socioaffective response in cannabis users.…”
Section: Discussionmentioning
confidence: 99%
“…Further, prior research indicates cannabis users may be particularly vulnerable to cognitive control and affective processing deficits, including when identifying emotional faces [ 59 ]. Cannabis users may have to use more neural resources to achieve the same level of performance [ 60 ], though this may not happen as readily on a less demanding task, such as on a congruent processing task. Future research should continue to investigate socioaffective response in cannabis users.…”
Section: Discussionmentioning
confidence: 99%
“…This review largely does not cover studies of domain-general risk-taking (see Sherman et al, 2018 ), non-human animal models (see Belin et al, 2016 ), brain structure (see Squeglia and Cservenka, 2017 ), or findings in adults over the age of 25 ( see Moeller and Paulus, 2017 ). Instead, this review builds upon previous discussions of adolescent neural function and substance use (e.g., Coronado et al, 2020 ; Courtney et al, 2019 ; Gray and Squeglia, 2017 ; Squeglia and Gray, 2016 ), contributing a new perspective about the importance of social and emotional information when understanding adolescent substance use. After applying exclusion criteria, the number of studies reviewed was 28 (see Table 2 ).…”
Section: Methods For Locating and Reviewing Studiesmentioning
confidence: 99%
“…Taken together, although findings are mixed, these studies consistently show functional impairments in various brain regions, from the frontal cortical engagement in executive processing to that of the limbic system in emotional regulation, with long term adolescent cannabis use. One recent review of fMRI studies in adolescent cannabis users reported results suggesting that cannabis users may require the recruitment of more neural resources than non-using peers to achieve compatible performance on tasks across domains [ 28 ]. The authors stipulate that the frontal and parietal lobes were often identified as key regions engaged across tasks [ 17 , 18 , 19 , 24 , 27 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors stipulate that the frontal and parietal lobes were often identified as key regions engaged across tasks [ 17 , 18 , 19 , 24 , 27 , 29 , 30 , 31 ]. Another important observation relates to results from a few preliminary longitudinal studies indicating that there may be pre-existing activation differences, especially in prefrontal cortical (PFC) regions, in teens who will initiate cannabis use [ 28 ]. However, quantitative assessments (e.g., meta-analyses) of existing reports with respect to activation patterns during distinct cognitive processes (e.g., executive control vs. reward vs. emotion paradigms), severity of use and the contribution of developmentally sensitive factors such as age and childhood comorbid disorders and the implications of possible findings to clinical presentations are presently lacking.…”
Section: Introductionmentioning
confidence: 99%